Evaluating Psychosocial Support Provided by an Augmented Reality Device for Children With Type 1 Diabetes. Issue 1 (June 2021) - Ullman, Daniel; Phillips, Elizabeth; Aladia, Salomi; Haas, Peter; Fowler, Halle S.; Iqbal, Iman S.; Mi, Kaitlyn L.; Riches, Isabel W.; Omori, Maya; Malle, Bertram F.
Type 1 diabetes (T1D), previously known as juvenile diabetes, has a large impact on everyday life and can pose a number of challenges for both children and their parents. A patient-centered design company, Sproutel, has designed and developed Jerry the Bear®—an interactive augmented reality (AR) stuffed animal toy bear designed to provide children with T1D with comfort and education about their diabetes management through play. We evaluated the AR device in a research study that involved participation over the course of approximately two weeks; the overall research project spanned three years and involved a variety of partners. We investigated whether Jerry the Bear offered psychosocial support to children with T1D and their parents and whether a new prototype version (equipped with audio feedback) offered any additional benefits. We conducted two versions of the study—a lab study ( n = 11) and a remote study without any in-person component ( n = 14). We found two major takeaways: (1) The results from the remote study closely paralleled the more time- and effort-intensive lab study, pointing to a promising avenue of research for hard-to-reach populations. (2) Jerry the Bear had a positive impact on children with T1D and their parents in almost all cases—in some the impact was more neutral, but never markedly negative. We did not find evidence for a consistent preference between the current Jerry the Bear and the new prototype. We also discuss the challenges of conducting rigorous research in highly specific target populations.